Cardiac Manifestations of Myotonic Dystrophy in a Pediatric Cohort - Brunet Garcia, Laia; Hajra, Ankita; Field, Ella; Wacher, Joseph; Walsh, Helen; Norrish, Gabrielle; Manzur, Adnan; Muntoni, Francesco; Munot, Pinki; Robb, Stephanie; Quinlivan, Rosaline; Scoto, Mariacristina; et al. (Frontiers in Pediatrics, 2022)
Myotonic dystrophy type 1 (DM1) is the most prevalent inherited neuromuscular dystrophy in adults. It is a multisystem disease with cardiac manifestations. Whilst these are well-defined in adults, there are scarce published data in the paediatric population. This study aimed to investigate the yield and progression of cardiac disease in paediatric DM1 patients, focusing on congenital DM1 (cDM1). Methods A retrospective observational study of all paediatric DM1 patients referred to our centre (December 2000-November 2020) was conducted. Patients were classified into DM1 forms according to age of symptom onset and disease severity. Patients underwent clinical and cardiac evaluation. Results 67 DM1 paediatric patients were included: 56 (83.6%) cDM1 and 11 (16.4%) non-cDM1. Median follow-up time of cDM1 patients was 8.0 [IQR 3.25-11.0] years. Forty-nine (87.5%) and forty-four (78.6%) cDM1 patients had baseline and follow-up 12-lead-ECG, respectively. Overall, 43 (87.8%) presented ECG abnormalities, most commonly in the form of asymptomatic conduction disease (n=23, 46.9%), of which 21 (42.9%) had first degree atrioventricular block. One (1.8%) underwent pacemaker implantation for syncope in the context of progressive conduction disease. 4 (7.1%) cDM1 patients died during follow up; including 3 who died suddenly with no clear cause of death. Conclusions This study is the first to analyse the prevalence and progression of ECG abnormalities in cDM1 paediatric patients. The high prevalence of abnormal findings, progressive changes and number of potentially associated events (1 pacemaker implantation and 3 unexplained sudden deaths) stresses the importance of systematic and continued cardiac evaluation of these patients.